Relasi Motif Kain Lurik Jawa dan Makna Spiritualitasnya: Kajian Filosofis, Sosiologis, dan Fenomenologis - Lestari Purwaningsih (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Batik is a global cultural heritage of the Indonesian nation. Various kinds of Indonesian batik motifs, one of which is the Javanese Lurik Motif. In Philosophical-Sociological-Phenomenological Studies, Lurik Motives are very close to the human life cycle. Using a critical discourse analysis approach, Philosophical-Sociological-Phenomenological studies, this paper describes the relationship between the Javanese Lurik Motifs and their spiritual meanings. Javanese lurik motifs have different meanings and uses in every traditional ceremony in society. It is hoped that this writing will be able to awaken the nationalism and love of the younger generation for Javanese Lurik Batik Motifs, their preservation in the future and increase our piety to the Creator, God Almighty.